Italian Society of Rheumatology recommendations for the management of gout - M. Manara; A. Bortoluzzi; M. Favero; I. Prevete; C.A. Scirè; G. Bianchi; C. Borghi; M. A. Cimmino; G. M. D'Avola; G. Desideri; G. Di Giacinto; M. Govoni; et al. (PAGEPress Publications, 2013)
Objective: Gout is the most common arthritis in adults. Despite the availability of valid therapeutic options, the management of patients with gout is still suboptimal. The Italian Society of Rheumatology (SIR) aimed to update, adapt to national contest and disseminate the 2006 EULAR recommendations for the management of gout. Methods: The multidisciplinary group of experts included rheumatologists, general practitioners, internists, geriatricians, nephrologists, cardiologists and evidence-based medicine experts. To maintain consistency with EULAR recommendations, a similar methodology was utilized by the Italian group. The original propositions were translated in Italian and priority research queries were identified through a Delphi consensus approach. A systematic search was conducted for selected queries. Efficacy and safety data on drugs reported in RCTs were combined in a meta-analysis where feasible. The strength of recommendation was measured by utilising the EULAR ordinal and visual analogue scales. Results: The original 12 propositions were translated and adapted to Italian context. Further evidences were collected about the role of diet in the non-pharmacological treatment of gout and the efficacy of oral corticosteroids and low-dose colchicine in the management of acute attacks. Statements concerning uricosuric treatments were withdrawn and replaced with a proposition focused on a new urate lowering agent, febuxostat. A research agenda was developed to identify topics still not adequately investigated concerning the management of gout. Conclusions: The SIR has developed updated recommendations for the management of gout adapted to the Italian healthcare system. Their implementation in clinical practice is expected to improve the management of patients with gout.